Grain-oriented electrical steel sheet and its manufacturing method
By optimizing laser irradiation conditions to control melting protrusions and maintaining specific groove dimensions, the challenges of forming grooves on directional electromagnetic steel sheets are addressed, resulting in improved iron loss reduction and productivity.
Patent Information
- Application Number
- JP2024501164
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-04
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2043-10-04
AI Technical Summary
Existing methods for forming grooves on directional electromagnetic steel sheets using laser irradiation face challenges such as molten protrusions that deteriorate magnetic properties and reduce productivity, as well as limitations in achieving high-speed processing and maintaining magnetic domain control effects.
The solution involves optimizing the laser irradiation conditions to control the shape of melting protrusions, ensuring that at least one crystal grain in the protrusion differs by 5° or more from the base steel sheet's crystal orientation, and maintaining specific dimensions for groove width, depth, and spacing, while omitting the protrusion removal process.
This approach enables the formation of directional electromagnetic steel sheets with improved iron loss reduction without compromising productivity, as the optimized protrusions enhance magnetic domain subdivision without the need for additional processing steps.
Smart Images

Figure 0007659219000004 
Figure 0007659219000005 
Figure 0007659219000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a grain-oriented electrical steel sheet. [Background technology]
[0002] Grain-oriented electrical steel sheet is a steel sheet whose crystal orientation is controlled by a combination of cold rolling and annealing so that the magnetization easy axis of the crystal grains coincides with the rolling direction.
[0003] Forming an insulating film on the surface of a base steel sheet with controlled crystal orientation is known as a technology for reducing eddy current loss, which is a type of iron loss in grain-oriented electrical steel sheets. The insulating film not only provides electrical insulation, but also tensile strength, rust resistance, etc. to the base steel sheet.
[0004] Another method for reducing eddy current loss is the magnetic domain control method, in which strain regions or grooves formed in a direction intersecting the rolling direction are formed at predetermined intervals along the rolling direction to narrow the width of the 180° magnetic domain (subdivide the 180° magnetic domain). Magnetic domain control methods are classified into a method of applying strain to the base steel sheet of the grain-oriented electrical steel sheet and a method of forming grooves on the surface of the base steel sheet where a coating that applies tension to the base steel sheet exists.
[0005] By using grain-oriented electrical steel sheets with grooves that have been subjected to magnetic domain control, the grooves do not disappear even when the transformer core (wound core) is manufactured and stress relief annealing is performed, so the magnetic domain refinement effect can be maintained. For this reason, magnetic domain control by groove formation is sometimes adopted for wound cores as a method of reducing eddy current loss.
[0006] Fig. 1 is a schematic diagram of an electrical steel sheet with grooves formed therein. Fig. 1 shows a state in which a plurality of grooves 2 are formed on the surface of a base steel sheet 1 at intervals in the rolling direction of the base steel sheet 1. In Fig. 1, the symbol θ indicates the angle between the longitudinal direction of the groove 2 and a direction perpendicular to the rolling direction and thickness direction of the base steel sheet 1 (the sheet width direction). The symbol W indicates the width of the groove 2, the symbol D indicates the depth of the groove 2, and the symbol P indicates the distance between adjacent grooves 2 in the rolling direction.
[0007] Various methods have been proposed for forming grooves in electrical steel sheets. For example, Patent Document 1 discloses an electrolytic etching method for forming grooves on the surface of a grain-oriented electrical steel sheet by electrolytic etching.
[0008] Patent Document 2 discloses a gear pressing method in which a gear is mechanically pressed onto the surface of a grain-oriented electrical steel sheet to form grooves on the surface of the steel sheet.
[0009] However, the electrolytic etching method requires masking, etching, and mask removal, which makes the process more complicated than the mechanical method. In the gear press method, the teeth wear out in a short period of time due to the high hardness of the magnetic steel sheet. Furthermore, from the perspective of high-speed processing, it is difficult to achieve a line speed of 100 mpm or more, which is required in general steel manufacturing processes.
[0010] Furthermore, Patent Document 3 discloses a laser irradiation method in which a laser irradiated portion of the steel sheet surface of a grain-oriented electrical steel sheet is melted and evaporated by laser irradiation. The laser irradiation method does not have the problems of tooth profile wear or complicated processes, and allows for high-speed processing. However, when grooves are formed by laser irradiation, molten protrusions are formed on the sides of the groove due to sputtering that occurs when forming the groove. As the molten protrusions deteriorate the magnetic properties, a process is required to remove the molten protrusions, which poses the problem of reduced productivity.
[0011] Furthermore, Patent Document 5 proposes that, since molten protrusions formed by groove formation through laser irradiation prevent close contact between adjacent grain-oriented electromagnetic steel sheets in a laminated core and increase noise, the size of the protrusions should be reduced and the metal structure of the protrusions should be oriented in the Goss orientation to maintain iron loss. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Special Publication No. 62-54873 [Patent Document 2] Special Publication No. 62-53579 [Patent Document 3] JP 2003-129135 A [Patent Document 4] International Publication No. 2011 / 007771 [Patent Document 5] International Publication No. 2017 / 171013 Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention was developed in view of the above problems, and has an object to provide a grain-oriented electrical steel sheet that improves iron loss while suppressing a decrease in productivity in magnetic domain control for forming laser grooves (grooves formed by laser irradiation). [Means for solving the problem]
[0014] The inventors have conducted intensive research to solve the above problems. While repeatedly examining the laser irradiation conditions when forming the laser grooves, they found conditions under which no adverse effect on iron loss is caused by controlling the shape of the molten protrusions (protrusions) that are generated on the side of the grooves adjacent to the grooves on the steel sheet surface due to sputtering generated during laser groove formation. As a result of further investigation, they found that iron loss is improved when crystal grains whose crystal orientation differs from that of the base steel sheet by 5° or more are present in the protrusions. This is a completely new finding not found in Patent Documents 3 and 5 regarding molten protrusions. The present invention was made based on these new findings, and the gist of the present invention is as follows.
[0015] [1] A grain-oriented electromagnetic steel sheet according to one embodiment of the present invention is a grain-oriented electromagnetic steel sheet having a plurality of grooves on its surface, characterized in that the steel sheet has a protrusion on the side of the groove adjacent to the groove on its surface, and the crystal orientation of at least one crystal grain present inside the protrusion differs by 5° or more from the crystal orientation of crystal grains present in parts of the electromagnetic steel sheet other than the protrusion. [2] The grain-oriented electrical steel sheet according to one embodiment of the present invention is the grain-oriented electrical steel sheet according to the item [1], characterized in that the average height of the protrusions is 2.5 μm or more and 10.0 μm or less. [3] The grain-oriented electrical steel sheet according to one embodiment of the present invention is the grain-oriented electrical steel sheet according to [1] or [2], characterized in that in the grain-oriented electrical steel sheet, the angle θ between the direction perpendicular to the rolling direction and the sheet thickness direction and the longitudinal direction of the groove is 40° or less, the width W of the groove is 20 μm or more and 300 μm or less, the depth D of the groove is 10 μm or more and 40 μm or less, and the spacing P of the groove in the rolling direction is 1 mm or more and 30 mm or less. [4] A method for producing a grain-oriented electrical steel sheet according to any one of the items [1] to [3], A method for producing grain-oriented electrical steel sheet, comprising a groove forming step of irradiating a laser onto a surface of a steel sheet to form grooves, characterized in that the laser beam irradiation conditions are such that a focused spot diameter dL of the laser beam in the rolling direction and a focused spot diameter dC of the laser beam in the sheet width direction satisfy formula (1). 1.0≦dL / dC ··· Formula (1) Effect of the Invention
[0016] According to the present invention, even if laser grooves are formed on the surface of the steel sheet, the protrusion removal process can be omitted, and a grain-oriented electrical steel sheet with good core loss can be obtained without reducing productivity. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a schematic diagram of an electromagnetic steel sheet in which grooves are formed. [Diagram 2] 1 is an optical microscope photograph of a cross section of a protrusion. [Diagram 3] This is an SEM image taken by SEM-EBSD of the cross section of the protrusion at an angle. [Figure 4] ND-IPF (Inverse Pole Figure) map of the field of view in Figure 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The inventors have conducted extensive research into how to maximize the magnetic domain refinement effect and increase productivity, and have found that if the molten protrusions present on the sides of the laser grooves (groove sides) on the steel sheet surface satisfy certain conditions, they do not adversely affect the magnetic properties. Hereinafter, the present invention will be described using a grain-oriented electrical steel sheet according to one embodiment of the present invention (hereinafter, abbreviated as this electrical steel sheet) as an example.
[0019] The present electrical steel sheet is an electrical steel sheet having a plurality of grooves arranged generally parallel to one another on its surface, as shown in Fig. 1, and may or may not have a glass coating on the steel sheet surface, and may or may not have a tensile coating (insulating coating) on the outermost surface of the steel sheet. Fig. 1 shows a conceptual diagram of the present electrical steel sheet having neither a glass coating nor a tensile coating. Unless otherwise specified, the steel sheet surface refers to the surface including a glass coating or a tensile coating when the steel sheet has such a coating.
[0020] <Protrusion> The grooves on the steel sheet surface are formed as protrusions on the sides of the groove on the steel sheet surface due to spatter (molten metal splashes) and molten metal flows that are generated when laser grooves are formed by irradiating a laser. As shown in Figure 1, protrusions 3 are formed along groove 2 on the surface of this electromagnetic steel sheet 1. In some cases, another protrusion may be formed on the steel sheet surface between protrusion 3 and protrusion 3 of the adjacent groove (i.e., on the steel sheet surface sandwiched between protrusions 3 on the sides of the groove), but the protrusions referred to in this electromagnetic steel sheet refer to the protrusions closest to the groove, i.e., the protrusions formed on the sides of the groove. Figures 2 to 4 are views of the grooves of this electromagnetic steel sheet in a cross section perpendicular to the longitudinal direction of the groove. The dotted line in Figure 2 indicates an imaginary line on the surface of the steel sheet (surface imaginary line), which is the line where the steel sheet surface is assumed to have been before the laser grooves were formed. As can be seen from Figure 2, when the laser grooves are formed, protrusions are formed on the parts of the steel sheet surface adjacent to the laser grooves (groove sides). The protrusions refer to the parts located above the surface imaginary line (upper part in the steel sheet surface direction).
[0021] <Fine crystal grains in the protrusions> In this electrical steel sheet, a protrusion is formed on the side of the steel sheet surface of a groove formed on a base steel sheet, and in a cross section perpendicular to the longitudinal direction of the groove, the protrusion has at least one fine crystal grain whose crystal orientation differs by 5° or more from the crystal grains of the base steel sheet (parts other than the protrusion that are not affected by laser irradiation). Specifically, as shown in Figures 2 and 3, in a cross section perpendicular to the longitudinal direction of the groove, even one of the crystal grains present in the protrusion has a crystal orientation of Goss orientation {110}, which is the crystal orientation of the base steel sheet. <001> (Hereinafter, this may be referred to as the "base material Goss orientation.") It is sufficient if the crystal grains present in the protrusion have a crystal orientation different from that of the base material steel sheet and are hereinafter referred to as "fine crystal grains."
[0022] Fine crystal grains can be obtained by irradiating a laser on a steel sheet after cold rolling, decarburization annealing, or finish annealing, or on a steel sheet to which a tension coating has been applied. When irradiated after cold rolling, recrystallized grains are formed inside the protrusions by decarburization annealing, and the orientation is not encroached on the Goss orientation of the base material by secondary recrystallization, but an orientation shifted by 5° or more from the Goss orientation of the base material remains. When irradiated after decarburization annealing, recrystallized grains are formed inside the protrusions by finish annealing, and the orientation is not encroached on the Goss orientation of the base material by secondary recrystallization, but an orientation shifted by 5° or more from the Goss orientation of the base material remains. When irradiated on a steel sheet after finish annealing or to which a tension coating has been applied, recrystallized grains are formed inside the protrusions by subsequent coating baking or recoating baking, which are shifted by 5° or more from the orientation of the base steel sheet that has become Goss oriented by secondary recrystallization.
[0023] The reason why the fine grains in the protrusions reduce iron loss is thought to be as follows. Magnetic domain refinement in grain-oriented electrical steel sheet occurs when the magnetic poles generated on the surface of the steel sheet increase magnetostatic energy, and to resolve this, new 180° magnetic walls are generated, narrowing the magnetic domain width. When the magnetic domain width is narrowed, the distance the magnetic wall moves when the steel sheet is magnetized becomes shorter, reducing energy loss during magnetic wall movement, i.e., reducing iron loss. For this reason, fine crystal grains become the starting points for magnetic poles, promoting the refinement of 180° magnetic domains and leading to reduced iron loss.
[0024] If the orientation difference between the fine crystal grains of the protrusions and the crystal grains of the base steel sheet is small, it will not become the starting point of magnetic pole generation, so the orientation difference between the fine crystal grains of the protrusions and the crystal grains of the base steel sheet is set to 5° or more. The crystal orientation difference is preferably 6° or more, 7° or more, 8° or more, 9° or more, 10° or more, 11° or more, 12° or more, 13° or more, 14° or more, 15° or more, 16° or more, 17° or more, 18° or more, 19° or more, or 20° or more. Note that since the orientation difference is sufficient as long as it becomes the starting point of magnetic pole generation, there is no upper limit to the crystal orientation difference between the fine crystal grains and the base steel sheet.
[0025] The observation of the fine crystal grains inside the protrusion can be performed by electrolytically polishing a cross section perpendicular to the longitudinal direction of the groove, and obtaining an inverse pole figure (IPF) map (crystal orientation map) using SEM-EBSD (Electron Backscattered Diffraction Pattern) and measuring it. Figure 4 shows an example of an IPF map of a protrusion by SEM-EBSD. Figure 3 shows an SEM-EBSD image with the same field of view as Figure 4. In addition, when a glass film is present, the glass film itself exists in the base material and is difficult to distinguish using an IPF map by EBSD, but by combining it with an SEM-EBSD image, it is possible to distinguish the glass film from the steel plate including the protrusion. As explained above, the IPF map of EBSD can identify the fine crystal grains in the protrusion, and further, the crystal orientation of the fine crystal grains and the Goss orientation of the base material can be confirmed.
[0026] If one or more fine crystal grains are present in one protrusion in a cross section perpendicular to the longitudinal direction of the groove, a magnetic pole is generated and a magnetic domain refinement effect is obtained. There is no particular upper limit on the number of fine crystal grains in one protrusion. For example, at least one arbitrary groove may be selected, and fine crystal grains may be observed by observing a cross section when cut in a cross section perpendicular to the longitudinal direction of the groove. In other words, one or more fine crystal grains may be observed per protrusion. There is no particular upper limit, but since too many fine crystal grains will increase the protrusion height, it may be 10 or less per protrusion.
[0027] If the size of the fine crystal grains becomes large, the magnetic properties may deteriorate, so the size of the fine crystal grains is preferably 15.0 μm or less in terms of the area equivalent circle diameter. Preferably, it is 14.0 μm or less, 13.0 μm or less, 12.0 μm or less, 11.0 μm or less, or 10.0 μm or less. There is no particular lower limit for the size of the fine crystal grains, but it may be 1.0 μm or more in consideration of the spatial resolution of EBSD.
[0028] The shape of the fine crystal grains is not particularly limited, but if the fine crystal grains are extremely long and flat in the rolling direction or thickness direction, the iron loss reduction effect may be reduced. Therefore, the shape ratio A, which is the ratio of the length of the fine crystal grains in the rolling direction to the length in the thickness direction, should be set to 0.2 to 5. Here, the shape ratio A of the fine crystal grains is calculated by dividing the maximum length L of the fine crystal grains in the rolling direction by the shape ratio A. RD and maximum length in the plate thickness direction L ND Ratio of L RD / L ND The lower limit of the shape ratio A of the fine crystal grains is preferably 0.25 or more, 0.3 or more, 0.4 or more, or 0.5 or more. The shape ratio A may be 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, or 1.5 or less. From the viewpoint of the magnetic pole generation starting point for reducing iron loss, it is preferable that the shape ratio is smaller than 1.0 (less than 1.0), that is, that is, that is elongated in the plate thickness direction, because it is considered that the magnetic pole generation starting point is easily formed by locally obstructing the flow of magnetic flux in the rolling direction, and therefore it is preferable.
[0029] <Protrusion height> Since the fine crystal grains promote the subdivision of magnetic domains, the height of the protrusion is not particularly limited. However, if the protrusion height is too low, the fine crystal grains become small and do not become the origin of magnetic poles, and there is no magnetic domain control effect, so the protrusion height should be 2.5 μm or more, preferably 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more. On the other hand, if the protrusion height is too high, the fine crystal grains become large, leading to a decrease in magnetic flux density, so the protrusion height should be 10.0 μm or less, preferably 9.0 μm or less.
[0030] The height of the protrusions can be measured, for example, with a non-contact or contact roughness meter such as a 3D microscope or a three-dimensional roughness meter (hereinafter collectively referred to as a "roughness meter") as follows. First, the roughness of the top of the protrusion on the steel plate surface is measured over a length of 150 μm parallel to the groove, and the maximum height of the protrusion is derived. Next, leaving the reference height unchanged, the roughness of the steel plate surface between that groove and an adjacent groove (preferably near the center between the grooves) is measured over a length of 150 μm parallel to the groove, and the average height of the steel plate surface between the grooves is measured. The difference between the obtained maximum height of the protrusion and the average height between the grooves is taken as the protrusion height.
[0031] Alternatively, the roughness distribution of the steel plate surface is measured by scanning the surface of the steel plate with a roughness gauge in a straight line perpendicular to the grooves, crossing the protrusions, and a cross-sectional profile is obtained. In this case, the height of the highest point of the protrusion relative to the position between adjacent grooves may be taken as the protrusion height. Alternatively, a virtual surface line may be drawn from the obtained cross-sectional profile, and the distance between the highest point of the protrusion and the virtual surface line may be taken as the protrusion height.
[0032] In this manner, the projection heights are measured at 10 random points on the steel plate, and the arithmetic mean of the projection heights thus measured is defined as the average projection height.
[0033] The average height of the protrusions may be measured by a method other than a roughness meter. For example, a cross section perpendicular to the longitudinal direction of the groove (such as the cross section shown in Figure 2) may be observed with an optical microscope, the height of the protrusions from the virtual line on the surface may be measured, and the maximum height may be taken as the protrusion height. This may be measured at 10 random points on the steel plate, and the arithmetic average of the protrusion heights at each measurement point may be defined as the average protrusion height. The average height of the protrusions may be measured by one of the above methods. When the average height of the protrusions is measured by a plurality of methods, the average height of the protrusions obtained by each method may be further averaged to obtain the average height of the protrusions.
[0034] In this electrical steel sheet, multiple grooves are formed on the surface of the steel sheet, generally parallel to each other in the rolling direction of the steel sheet, as shown in Figure 1. The groove direction (angle θ), groove width W, depth D, and spacing P are determined taking into account iron loss, as in the case of ordinary grain-oriented electrical steel sheets.
[0035] <Angle θ between the longitudinal direction of the base steel plate and the longitudinal direction of the groove> The angle θ between the direction perpendicular to the rolling direction and thickness direction of the base steel sheet (sheet width direction) and the longitudinal direction of the groove is set to 40° or less, because if it is too large, there will be no magnetic domain control effect and the iron loss improvement effect will not be obtained. The angle θ is preferably small, and is preferably 35° or less, 30° or less, 25° or less, 20° or less, 15° or less, 10° or less, 8° or less, 6° or less, or 5° or less. The lower limit of the angle θ is 0°, that is, when the longitudinal direction of the groove is parallel to the sheet width direction. The direction of the angle θ is not important, and refers to the acute angle of the angle formed by the longitudinal direction of the groove and the sheet width direction. A plurality of grooves are arranged approximately parallel to the surface of the base steel sheet, and the angle θ of each groove may be within the range described above.
[0036] <Groove width W> The groove width W refers to the width of the groove on the surface of the base steel sheet in the cross section (groove cross section) of the groove on a plane perpendicular to the longitudinal direction of the groove. If the groove width W is too narrow, it will not become the starting point of magnetic pole generation, there will be no magnetic domain control effect, and good iron loss will not be obtained, so it is set to 20 μm or more. On the other hand, if it is too wide, it will not become the starting point of magnetic pole generation, there will be no magnetic domain control effect, only the magnetic flux density will be significantly reduced, and good iron loss will not be obtained, so it is set to 300 μm or less. Therefore, the groove width W should be 20 μm or more and 300 μm or less. The lower limit of the groove width W is preferably 25 μm or 30 μm. The upper limit of the groove width W is preferably 250 μm, 200 μm, 150 μm, 100 μm, or 80 μm.
[0037] <Groove depth D> If the groove depth D is too shallow, it will not become the starting point of the magnetic pole, there will be no magnetic domain control effect, and good iron loss will not be obtained, so it is preferable that it is 10 μm or more. On the other hand, if it is too deep, exceeding 40 μm, the magnetic domain control effect will reach saturation, and only the magnetic flux density will drop significantly, so good iron loss will not be obtained. Therefore, the groove depth D should be 10 μm or more and 40 μm or less. The lower limit of the groove depth D is preferably 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm. The upper limit of the groove depth D is preferably 38 μm, 36 μm, 34 μm, 32 μm, 30 μm, 28 μm, or 26 μm.
[0038] <Groove Spacing P> The groove spacing P is the distance between the longitudinal groove center lines of adjacent grooves arranged approximately parallel to each other on the steel sheet surface, and refers to the distance in the rolling direction of the base steel sheet. The groove center line is a line parallel to the longitudinal direction of the groove that passes through the midpoint of the groove on the imaginary surface in the groove cross section.
[0039] If the groove interval P is too narrow, the magnetic domain control effect is saturated and only the magnetic flux density is significantly reduced, so good iron loss cannot be obtained, so it is preferable to set it to 1 mm or more. On the other hand, if it is too wide, exceeding 30 mm, the magnetic domain control effect is not sufficiently obtained and good iron loss cannot be obtained. Therefore, the groove interval P is preferably 1 mm or more and 30 mm or less. The groove interval P does not have to be equal, but the groove interval P between adjacent grooves should be within the above range. The lower limit of the groove interval P is preferably 1.2 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.8 mm, or 2.0 mm. The upper limit of the groove interval P is preferably 25.0 mm, 20.0 mm, 15.0 mm, 10.0 mm, 7.0 mm, or 5.0 mm.
[0040] <Manufacturing method> First, a cold-rolled steel sheet for the present electrical steel sheet is manufactured by a known method. The steel sheet components and the manufacturing method of the cold-rolled steel sheet are not particularly limited, and known methods, such as the steel sheet components and steel sheet manufacturing methods described in Patent Documents 4 and 5, can be used.
[0041] In a known manner, the cold-rolled steel sheet is decarburized and nitrided, then coated with an annealing separator, heated, held, and cooled. In order to enhance the magnetic domain control effect, a tension film (insulating film) may be formed on the steel sheet.
[0042] The decarburization conditions can be known. For example, the temperature is raised to 850° C., held for 60 seconds, and then cooled. The decarburization atmosphere is a hydrogen-inert gas atmosphere. H2O / P H2 is preferably in the range of 0.15 to 0.80, and particularly in the range of 0.30 to 0.60, excellent characteristics can be obtained.
[0043] The nitriding can be carried out by a known method. The amount of nitriding can be set within the range of, for example, 50 to 400 ppm, but particularly favorable characteristics can be obtained within the range of 180 to 250 ppm.
[0044] The composition of the annealing separator may be a known one. When a glass film is formed on the steel sheet surface, for example, MgO: 100 parts by mass, TiO 2 5 parts by weight, and the additive is, for example, FeCl 2 In addition, when a glass film is not formed on the steel sheet surface, for example, alumina (Al 2 O 3 ) based annealing separator is used.
[0045] The glass film is formed by winding a steel sheet coated with an annealing separator into a coil, holding it at 1150 to 1250°C for 10 to 30 hours, and then cooling it. The composition of the annealing separator may be a known one, for example, MgO: 100 parts by mass, TiO 2 5 parts by weight, and the additive is, for example, FeCl 2 can be added so that the chlorine content is 200 ppm.
[0046] Thereafter, an insulating film coating is applied and baked. There is no particular limitation on the type of insulating film, and any conventionally known insulating film is suitable for the grain-oriented electrical steel sheet.
[0047] An example of the insulating film is a film formed by applying an aqueous coating solution containing a phosphate and colloidal silica. In this case, examples of the phosphate include phosphates such as Ca, Al, and Sr. Among them, aluminum phosphate is more preferable. It is preferable to form a tensile insulating film by applying the insulating film coating liquid to the surface of the steel sheet by a wet application method such as a roll coater, and baking it in an air atmosphere at a temperature of 800 to 900°C for 10 to 60 seconds. Recoating and baking may be performed.
[0048] Laser irradiation is performed on steel sheets after cold rolling, decarburization annealing, decarburization nitriding annealing, or finish annealing, or on steel sheets to which a tension coating has been applied. It is preferable that the protrusions formed by laser irradiation remain easily until the steel sheet after the final process. For example, when irradiating a steel sheet after cold rolling, it is preferable to irradiate the steel sheet with a laser after removing the cold rolling oil. By removing the excess oil, the energy of the laser becomes easier to transmit to the steel sheet, and if there is an oil film between the steel sheet surface and the spatter, the spatter becomes easier to peel off. When irradiating a steel sheet after decarburization annealing, it is preferable to irradiate the steel sheet with a laser before applying an annealing separator. When irradiating after cold rolling, recrystallized grains are formed in the inside of the protrusions by decarburization annealing, and when irradiating after decarburization annealing, recrystallized grains are formed by finish annealing, and the orientation shifted by 5° or more from the Goss orientation of the base material remains without being eroded by the Goss orientation of the base material by secondary recrystallization. When irradiating a steel sheet after finish annealing, it is also possible to irradiate the steel sheet with a laser before applying an insulating coating. When irradiated to steel sheets that have been finish annealed or that have been given a tension coating, recrystallized grains that are displaced by 5° or more from the orientation of the base steel sheet, which has a Goss orientation due to secondary recrystallization, are formed inside the protrusions during the subsequent coating baking or recoating baking.
[0049] <Groove formation process: Laser irradiation conditions> Next, a laser is irradiated to the steel sheet after cold rolling, decarburization annealing, decarbonitriding annealing, or finish annealing, or to the steel sheet further provided with a tension coating, to form a plurality of grooves on the surface of the steel sheet in a direction intersecting the rolling direction such that the groove width W, groove depth D, and predetermined interval (groove interval P) are within a specified range (groove formation process). Among the laser irradiation conditions, the type of laser light source, the laser output, the laser scanning speed, and the steel sheet moving speed during laser irradiation are not particularly limited, but it is sufficient to appropriately select conditions under which not only the groove width W, groove depth D, and predetermined interval (groove interval P) of the grooves, but also the protrusions and the fine crystal grains therein are within the specified range. Since the conditions vary depending on the apparatus, atmosphere, and the presence or absence of a coating, for example, it is sufficient to perform a test laser irradiation in advance to derive appropriate conditions.
[0050] [Laser light source] As the laser light source, for example, a high-power laser generally used for industrial purposes such as a fiber laser, a YAG laser, a semiconductor laser, or a CO2 laser can be used. As long as the grooves can be stably formed, a pulsed laser or a continuous wave laser can be used.
[0051] [Laser output] If the laser output is too small, the laser scanning speed to form the desired grooves will drop significantly, resulting in a drop in industrial productivity, so it is recommended that the laser output be 200 W or more. It is preferably 1000 W or more, and more preferably 1500 W or more. If the laser output is too large, the power supply capacity will increase, resulting in huge equipment costs, making it industrially unrealistic, so it is recommended that the laser output be 3000 W or less. It is preferably 2800 W or less, and more preferably 2500 W or less.
[0052] [Laser scanning speed] If the laser scanning speed is too slow, the steel sheet passing speed must be slowed down, resulting in reduced productivity, and therefore the speed is set to 5 m / s or more. It is preferably set to 20 m / s or more, and more preferably set to 40 m / s or more. If the laser scanning speed is too fast, a higher output is required, which increases equipment costs, and therefore the speed is set to 100 m / s or less. It is preferably set to 80 m / s or less, and more preferably set to 60 m / s or less.
[0053] [Laser light focusing spot shape] By forming the focused spot shape of the laser beam on the surface of the base steel sheet to be circular or elliptical slightly expanding in the rolling direction, protrusions can be efficiently formed on the surface of the steel sheet. The conditions for irradiating the laser beam may be, for example, such that the focused spot diameter dL of the laser beam in the rolling direction is 5 to 100 μm, the focused spot diameter dC of the laser beam in the sheet width direction is 5 to 100 μm, the laser output is 200 to 3000 W, and the laser scanning speed V is 5 to 100 m / s, thereby satisfying formula (1). dL / dC≧1.0 ··· Formula (1)
[0054] When dL / dC is greater than 1.0, the laser spot diameter becomes elongated elliptical in the rolling direction, and a molten protrusion is formed. Even when dL / dC is less than 1.0, a protrusion is formed, but a part of the molten sputter accumulates inside the groove, and the protrusion height is low. The lower limit of dL / dC is preferably 1.1, 1.2, 1.3, 1.5, 1.7, or 2.0. There is no particular restriction on the upper limit of dL / dC, but when dL / dC is too large, the groove width becomes wide and the magnetic domain control effect by the groove cannot be enjoyed, so it is preferably 30.0, 25.0, 20.0, 18.0, 15.0, or 10.0.
[0055] The diameter of the focused spot is not particularly limited as long as the relationship defined by dL and dC is satisfied, but the diameter of the focused spot should be selected so that the groove width is less than 300 μm and in relation to other properties of the electrical steel sheet. For example, the upper limit of dC is 300 μm, preferably 280 μm, 250 μm, 200 μm, 150 μm, or 100 μm.
[0056] [Assist gas] Simultaneously with the irradiation of the laser light, an assist gas is sprayed onto the portion of the steel sheet to be irradiated with the laser light. The assist gas plays a role in removing components melted or evaporated from the steel sheet by the laser irradiation. By spraying the assist gas, the laser light reaches the steel sheet stably, so that grooves are formed stably. The flow rate of the assist gas is preferably, for example, 10 to 1000 liters per minute. The assist gas is preferably air or an inert gas.
[0057] [Omission of the protrusion removal process] Since the present electrical steel sheet has fine crystal grains in the protrusions, which improves iron loss, the protrusion removal process is omitted. In other words, there is no need for the protrusion removal process after laser groove formation, which was a problem in the past, and there is no corresponding decrease in productivity. EXAMPLES
[0058] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely examples of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these examples. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.
[0059] <Example 1> A slab containing 3.3 mass% Si, 0.10 mass% Mn, 0.006 mass% S, 0.060 mass% C, 0.027 mass% acid-soluble Al, 0.008 mass% N, and the remainder being Fe and impurities, was hot-rolled by a known method, annealed as a hot-rolled sheet, and cold-rolled to a final thickness of 0.22 mm to obtain steel sheets A1 to A12 and a1 to a12.
[0060] Next, for A1 to A3 and a1 to a3, the surface of the steel plate was irradiated with a laser to form multiple grooves extending in a direction intersecting the rolling direction at intervals of 3 mm in the rolling direction. The groove formation direction was inclined at 10° to the L direction (rolling direction) with respect to the C direction (plate width direction) of the steel plate, and the laser light output was controlled at 1500 to 2000 W so that the groove depth was 25 μm. The groove width was in the range of 40 to 220 μm.
[0061] The focal spot diameter dL of the laser beam in the rolling direction was adjusted to 25 to 120 μm, and the focal spot diameter dC of the laser beam in the plate width direction was adjusted to 25 to 140 μm. The laser scanning speed was 45 m / s. During laser irradiation, air assist gas was blown at 100 liters / min to efficiently remove the metal of the steel plate that was melted and evaporated by the laser.
[0062] Steel sheets (cold-rolled sheets) A1 to A3, a1 to a3 in which grooves were formed by laser irradiation after cold rolling, and steel sheets A4 to A12 and a4 to a12 without grooves were decarburized and further subjected to nitriding treatment. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere, with a partial pressure ratio of water vapor and hydrogen of PH 2 O / PH 2 The amount of nitriding was set to 200 ppm.
[0063] Regarding the steel plates (decarbonitrided plates) A4 to A6 and a4 to a6 in which grooves were formed by laser irradiation after decarbonitriding treatment, the laser was irradiated under the same conditions as above to form grooves of the same shape.
[0064] Thereafter, the steel sheets A1 to A12 and a1 to a12 were coated with an annealing separator mainly composed of MgO at a coating amount of 4 g / m on one side. 2 The composition of the annealing separator was 100 parts by mass of MgO, 5 parts by mass of TiO2, and 100 parts by mass of FeCl 2 was added to give a chlorine content of 200 ppm.
[0065] The steel sheet was then wound into a coil and held at a maximum temperature of 1200°C for 20 hours before being cooled to form a glass film on the surface.
[0066] Regarding the steel plates (glass plates) A7 to A9 and a7 to a9, on whose surfaces grooves were formed by laser irradiation after a glass film was formed, the laser was irradiated under the same conditions as above to form grooves of the same shape.
[0067] Thereafter, a tension coating containing aluminum phosphate as a main component was formed on the steel sheets A1 to A12 and a1 to a12 to a thickness of 1 μm. The tension in this case was 12 MPa in the rolling direction including the glass coating.
[0068] For the steel plates (tensile-coated plates) A10 to A12 and a10 to a12 in which grooves were formed by laser irradiation after tensile coating, the grooves were formed by irradiating the steel plates with a laser under the same conditions as described above.
[0069] Thereafter, for A10 to A12 and a10 to a12, a tensile film mainly composed of aluminum phosphate was formed again to a thickness of 1 μm.
[0070] A1 to A12 and a1 to a12 are iron losses W 17 / 50 (Energy loss measured under excitation conditions of 1.7 T and 50 Hz) The results are shown in Table 1.
[0071] In Examples A1 to A12 and Comparative Examples a1 to a12, the groove angle, groove depth, and groove spacing conditions that affect iron loss are all the same, and the magnetic flux density is all about the same. However, while Examples 1 to 12 have good iron loss of less than 0.750 W / kg, Comparative Examples a1 to a12 have iron loss of 0.750 W / kg or more, which is poor. In Examples A1 to A12, cross-sectional EBSD observation showed that fine crystal grains existed in the protrusions, and their crystal orientation was deviated from the Goss orientation of the base material by 5° or more. When there were two or more fine crystal grains in the protrusions, the deviation angle from the Goss orientation of the base material was recorded. The shape of the protrusions and the properties of the microcrystalline grains within the protrusions were measured by randomly selecting three grooves within the steel plate, measuring one randomly selected cross section for each groove using the method described above, and then calculating the arithmetic average of the measured values.
[0072] <Example 2> A slab containing 3.3 mass% Si, 0.10 mass% Mn, 0.006 mass% S, 0.060 mass% C, 0.027 mass% acid-soluble Al, 0.008 mass% N, and the remainder being Fe and impurities, was hot-rolled by a known method, annealed as a hot-rolled sheet, and cold-rolled to a final thickness of 0.22 mm to obtain steel sheets B1 to B12.
[0073] Next, for steel sheets B1 to B3, a laser was irradiated onto the surface of the steel sheet to form a plurality of grooves extending in a direction intersecting the rolling direction at intervals of 5 mm along the rolling direction. The groove forming direction was inclined 5° to the L direction with respect to the C direction of the steel sheet, and the laser light output was controlled in the range of 1800 to 2300 W so that the groove depth was 30 μm. The groove width was 35 to 50 μm.
[0074] The focused spot diameter of the laser beam in the rolling direction was controlled to be in the range of 90 to 100 μm, and the focused spot diameter in the plate width direction was controlled to be in the range of 5 to 10 μm. The laser scanning speed was set to 60 m / s. During laser irradiation, air assist gas was blown at 100 liters / min to efficiently remove the metal of the steel plate that had been melted and evaporated by the laser.
[0075] Steel sheets B1 to B3, which had grooves formed by laser irradiation after cold rolling, and cold-rolled steel sheets B4 to B12, which had no grooves, were decarburized and then subjected to nitriding. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere, with a pH 2 O / PH 2 The amount of nitriding was set to 200 ppm.
[0076] The decarbonitrided steel sheets B4 to B6 were irradiated with a laser under the same conditions as above, and grooves of the same shape were formed.
[0077] Then, B1 to B12 were coated with an annealing separator mainly composed of MgO at a coating amount of 4 g / m on one side. 2 The composition of the annealing separator was 100 parts by mass of MgO, 100 parts by mass of TiO 2 : 5 parts by weight of FeCl 2 was added to give a chlorine content of 200 ppm.
[0078] Next, the steel plate was wound into a coil and held at a maximum temperature of 1200°C for 20 hours, after which it was cooled to form a glass film on the surface, thereby obtaining a glass plate.
[0079] Glass plates B7 to B9 were irradiated with a laser under the same conditions as above to form grooves of the same shape.
[0080] Thereafter, a tensile coating mainly composed of aluminum phosphate was formed to a thickness of 1 μm on B1 to B12 to obtain a tensile coated plate. The tension in this case was 12 MPa in the rolling direction including the glass coating.
[0081] For the tensile film plates B10 to B12, the laser was irradiated under the same conditions as above to form grooves of the same shape.
[0082] Thereafter, for B10 to B12, a tensile film containing aluminum phosphate as a main component was formed again to a thickness of 1 μm.
[0083] B1 to B12 are iron losses W 17 / 50(Energy loss measured under excitation conditions of 1.7 T and 50 Hz) The results are shown in Table 2.
[0084] In invention examples B1 to B12, the iron loss was even better at less than 0.730 W / kg, and the groove height of the protrusions in 3D microscope observation was all between 4 μm and 10 μm.
[0085] <Example 3> A slab containing 3.3 mass% Si, 0.10 mass% Mn, 0.006 mass% S, 0.060 mass% C, 0.027 mass% acid-soluble Al, 0.008 mass% N, and the remainder being Fe and impurities, was hot-rolled by a known method, annealed as a hot-rolled sheet, and cold-rolled to a final thickness of 0.22 mm to obtain steel sheets C1 to C8.
[0086] Next, the surface of the steel sheet was irradiated with a laser to form multiple grooves extending in a direction intersecting the rolling direction at intervals of 1 to 25 mm along the rolling direction. The groove formation direction was inclined at 0 to 40° to the L direction with respect to the C direction of the steel sheet, and the groove depth was 11 to 35 μm and the groove width was 20 to 290 μm.
[0087] The laser irradiation conditions were controlled to a laser output of 1500-2500W, a focused spot diameter of the laser in the rolling direction of 100-300μm, and a focused spot diameter of the laser in the sheet width direction of 10-250μm. The laser scanning speed was 60m / s. During the laser irradiation, air assist gas was sprayed at 100 liters / min to efficiently remove the metal of the steel sheet that had been melted and evaporated by the laser.
[0088] The cold-rolled steel sheet with the grooves was decarburized and then nitrided. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere, with a pH 2 O / PH 2 The amount of nitriding was set to 200 ppm.
[0089] After that, an annealing separator mainly composed of MgO was applied at a rate of 4 g / m on one side. 2The composition of the annealing separator was 100 parts by mass of MgO, 100 parts by mass of TiO 2 : 5 parts by weight of FeCl 2 was added to give a chlorine content of 200 ppm.
[0090] Next, the steel plate was wound into a coil and held at a maximum temperature of 1200°C for 20 hours, after which it was cooled to form a glass film on the surface, thereby obtaining a glass plate.
[0091] Furthermore, a tensile coating mainly composed of aluminum phosphate was formed to a thickness of 1 μm to obtain a tensile-coated plate. The tension in this case was 12 MPa in the rolling direction, including the glass coating.
[0092] C1 to C8 are iron losses W 17 / 50 (Energy loss measured under excitation conditions of 1.7 T and 50 Hz) The results are shown in Table 3.
[0093] In invention examples C1 to C8, the iron loss was good at less than 0.750 W / kg, the absolute value of the angle θ formed with the longitudinal direction of the groove was 0 to 40°, the width W of the groove was 20 to 300 μm, the depth D of the groove was 10 to 40 μm, and the spacing P of the groove in the rolling direction was 1 to 30 mm.
[0094] <Example 4> The frequency of fine crystal grains and the aspect ratio of fine crystal grains were measured for some of the samples produced in Examples 1 to 3, and the results are shown in Table 4. It was confirmed that the magnetic properties are good when the frequency of fine grains per protrusion is 0.05 to 10, and the aspect ratio of the fine grains in the protrusion is in the range of 0.2 to 5.
[0095] [Table 1]
[0096] [Table 2]
[0097] [Table 3] [Industrial Applicability]
[0098] 1 Steel plate (base material steel plate) 2 grooves 3 Protrusion 4 Surface virtual line 5. Fine grains θ Groove angle W Groove width D Groove Depth P Groove Spacing [Explanation of symbols]
[0099] 1 Steel plate (base material steel plate) 2 grooves 3 Protrusion 4 Surface virtual line 5. Fine grains θ Groove angle W Groove width D Groove Depth d Groove Spacing
Claims
1. A grain-oriented electrical steel sheet having a plurality of grooves on its surface, characterized in that the steel sheet has a protrusion on a side of the groove adjacent to the groove on its surface, the protrusion has an average height of 4 μm or more and 10 μm or less, and the crystal orientation of at least one crystal grain present inside the protrusion differs by 8° or more from the Goss orientation {110}<001>, which is the crystal orientation of crystal grains present in parts of the steel sheet other than the protrusion.
2. 2. The grain-oriented electrical steel sheet according to claim 1, characterized in that an angle θ between a direction perpendicular to the rolling direction and the sheet thickness direction and a longitudinal direction of the groove is 40° or less, a width W of the groove is 20 μm or more and 300 μm or less, a depth D of the groove is 10 μm or more and 40 μm or less, and a spacing P of the groove in the rolling direction is 1 mm or more and 30 mm or less.
3. A method for producing the grain-oriented electrical steel sheet according to claim 1 or 2, The groove forming step includes irradiating a laser beam onto a surface of a steel sheet to form a groove, and the laser beam irradiation conditions include: The laser scanning speed is 5 m / s or more and 100 m / s or less, and the laser output is 200 W or more and 3000 W or less, A method for producing a grain-oriented electrical steel sheet, characterized in that a focused spot diameter dL of laser light in the rolling direction and a focused spot diameter dC in the sheet width direction satisfy formulas (1) to (3). 1.0≦dL / dC... Formula (1) 5μm≦dL≦100μm...Formula (2) 5μm≦dC≦100μm...Formula (3)
Citation Information
Patent Citations
Portable receiver
JP1987053579A
Fixed-head type digital magnetic reproducing device
JP1987054873A
Method for manufacturing grain-oriented electromagnetic steel sheet with low core loss
JP2003129135A
Method for producing grain-oriented electromagnetic steel sheet
JP2012087332A
Stress relief annealed laser scribed grain oriented silicon steel and method for its manufacture
JP2020514548A